How Does the Students’ Readability in Mastering English Material? - Atik Rokhayani (Universitas Islam Negeri Walisongo Semarang, 2017)
In English class, the teachers/lecturers have to take a big chance in managing their students well. Managing the class is not an easy thing to do. The lecturers have to use appropriate techniques to gain the students attention. In university level, the students are the central in English teaching and learning process. They have many different characteristics and readability. From this atmosphere, the lecturer has to be ready for those differences. In selecting the English materials, the lecturer should consider based on the students’ needs. The paper aims at investigating the students’ readability in English class in mastering English material. It focuses on Intermediate Grammar Class. It describes the students who like watching English movies. The material focuses on simple past tense. The method of this study is descriptive qualitative research. This result shows that the mean score from the students who like watching English movies is 77.83. From the mean score, the mastery of simple past tense of the students who like watching English movies can be categorized as good. It can be used as the contribution to English teaching and learning process and reference for further researchers in doing the similar research.